A protocol for feasibility of plasma based GeneXpert platform and Dried Blood Spot (DBS) based Abbott platform for HIV-1 viral load testing among the people living with HIV attending ART centers in India. - Suchit Kamble; Pallavi Shidhaye; Anupam Mukherjee; Madhuri Tak; Shilpa Bembalkar; Sumit Aggarwal; Arpita Deb; Neha Kapoor; Vinita Verma; Chinmoyee Das; Smita Kulkarni; Manisha Ghate; et al. (PLoS ONE, 2023)
Background HIV-1 Viral load (VL) measures efficiency of the antiretroviral therapy (ART) after treatment initiation and helps to diagnose virological failures at an early stage. Current VL assays require sophisticated laboratory facilities. As well as there are other challenges pertaining to insufficient laboratory access, cold-chain management and sample transportation. Hence the number of HIV-1 VL testing laboratories is inadequate in the resource limited settings. The revised national tuberculosis elimination programme (NTEP) in India has developed a vast network of point of care (PoC) testing facilities for diagnosis of tuberculosis and several GeneXpert platforms are functional under this programme. Both the GeneXpert HIV-1 assay and HIV-1 Abbott real time assay are comparable and GeneXpert HIV-1 assay can be used as PoC for HIV-1 Viral load testing. Also, the dried blood spot (DBS) as a sample type has been considered as a good option for HIV-1 VL testing in hard to reach areas. This protocol is therefore developed to assess the feasibility of integrating HIV-1 VL testing among people living with HIV (PLHIV) attending ART centres using the two public health models under the current programme: 1. HIV-1 VL testing using GeneXpert platform and plasma as a sample type, and 2. HIV-1 VL testing using Abbott m2000 platform and DBS as a sample type. Methods This ethically approved feasibility study will be implemented at two moderate to high burden ART centres where VL testing facility is not available in the town. Under Model-1, arrangements will be made to carry out VL testing on the adjacent GeneXpert facility and under Model-2, DBS will be prepared on site and couriered to identified viral load testing laboratories. In order to assess the feasibility, data will be collected on pretested questionnaire pertaining to number of samples tested for VL testing, number of samples tested for tuberculosis (TB) diagnosis and the turnaround time (TAT). In-depth interviews will be conducted among the service providers at ART centre and different laboratories for addressing any issues regarding the model implementation. Results The proportion of PLHIV tested for VL at ART centres, total TAT for both models including TAT for sample transportation, sample testing and receipt of results as well as proportion of sample rejections and reasons for the same, correlation coefficient between DBS based and plasma based VL testing will be estimated using various statistical tools. Conclusion If found promising, these public health approaches will be helpful for the policy makers and program implementation in scaling up HIV-1 viral load testing within India.